These stones will shout : a new voice for the Old Testament - Link, Mark J. (Niles, IL : Argus Communications, 1975)
Discusses the evidence revealed by modern archaeological discoveries that supports the accuracy of the Old Testament in historical particulars.
Includes bibliographical references and index.
Keywords: Bible. -- Antiquities; Bible. -- interpretation issues; Bible. -- History of contemporary events; Bible. -- History of Biblical events; Bible. -- Criticism, interpretation, etc